Wide disparities in attitudes and practices regarding Type II sphincter of Oddi dysfunction: a survey of expert U.S. endoscopists - Watson, Rabindra R.; Klapman, Jason; Komanduri, Srinadh; Shah, Janak N.; Wani, Sachin; Muthusamy, Raman (Endoscopy International Open, 2016)
Background: Sphincter of Oddi manometry (SOM) is recommended in the evaluation of suspected Type II sphincter of Oddi dysfunction (SOD2), though its utility is uncertain. Little is known about the practice of expert endoscopists in the United States regarding SOD2.Methods: An anonymous electronic survey was distributed to 128 expert biliary endoscopists identified from U.S. advanced endoscopy training programs.Results: The response rate was 46.1 % (59/128). Only 55.6 % received training in SOM, and 49.2 % currently perform SOM. For biliary SOD2, 33.3 % routinely obtain SOM, 33.3 % perform empiric sphincterotomy, and 26.3 % perform single session endoscopic ultrasound/endoscopic retrograde cholangiopancreatography (EUS/ERCP). In contrast, an equal number (35.1 %) favor SOM or single session EUS/ERCP for suspected acute idiopathic recurrent pancreatitis, while 19.3 % would perform empiric sphincterotomy. Those who perform SOM believe it to be important in predicting response to treatment compared with those who do not (71.8 % vs 23.1 %, P = 0.01). Yet only 51.7 % of this group performs SOM for suspected SOD2. Most (78.6 %) believe that < 50 % of patients report improvement in symptoms after sphincterotomy. Common reasons for not obtaining SOM included unreliable results (50 %), and procedure-related risks (39.3 %). Most (59.3 %) believe SOD2 is at least in part a functional disorder; only 3.7 % felt SOD is a legitimate disorder of the sphincter of Oddi.Conclusions: Our survey of U.S. expert endoscopists suggests that SOM is not routinely performed for SOD2 and concerns regarding its associated risks and validity persist. Most endoscopists believe SOD2 is at least in part a functional disorder that will not respond to sphincterotomy in the majority of cases.